(untitled) (Journal of Computational Mathematics, 1985)
A general approach of deferred correction procedure based on linear multistep formulas is proposed. Several deferred correction procedures based on backward differentiation formulas, which allow us to develop L-stable algorithms of order up to 4 and L(α)-stable algorithms of order up to 7, are derived. Preliminary numerical results indicate that this approach is indeed efficient.